2020
DOI: 10.3171/2020.5.focus20192
|View full text |Cite
|
Sign up to set email alerts
|

The association between lower Hounsfield units of the upper instrumented vertebra and proximal junctional kyphosis in adult spinal deformity surgery with a minimum 2-year follow-up

Abstract: OBJECTIVEPatients undergoing long-segment fusions from the lower thoracic (LT) spine to the sacrum for adult spinal deformity (ASD) correction are at risk for proximal junctional kyphosis (PJK). One mechanism of PJK is fracture of the upper instrumented vertebra (UIV) or higher (UIV+1), which may be related to bone mineral density (BMD). Because Hounsfield units (HUs) on CT correlate with BMD, the authors evaluated whether HU values were correlated with PJK after long fusions for ASD.METHODSThe authors perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…In the lumbar region, a few studies have shown a correlation between lower HU values and screw loosening 13 , 14 . According to a previous study by Duan et al 18 , lower HU values were associated with proximal junctional kyphosis in patients who underwent long-segmental fusions involving the lower thoracic spine. Our results also demonstrated a difference in HU values between the loosening and control groups at the lower thoracic level.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the lumbar region, a few studies have shown a correlation between lower HU values and screw loosening 13 , 14 . According to a previous study by Duan et al 18 , lower HU values were associated with proximal junctional kyphosis in patients who underwent long-segmental fusions involving the lower thoracic spine. Our results also demonstrated a difference in HU values between the loosening and control groups at the lower thoracic level.…”
Section: Discussionmentioning
confidence: 86%
“…Duan et al 18 suggested a cutoff value of 104 HU for predicting the risk of proximal junctional kyphosis in the lower thoracic spine (T9–T12). A higher cutoff value of 126 HU was derived from our study.…”
Section: Discussionmentioning
confidence: 99%
“…35 Poor bone quality, Parkinson disease, infection, smoking are well known risk factors for proximal junctional failure in spine surgery, but an unbalanced or hyper corrected spine is now considered as one of the main reasons for implant and junctional failure. 36,37 Our study has some limitations. First, this is a retrospective analysis from electronic medical records of 8 institutions in Latin America and selection bias could be present as there could be patients not properly included in the analysis due to its retrospective nature.…”
Section: Discussionmentioning
confidence: 93%
“…35 Poor bone quality, Parkinson disease, infection, smoking are well known risk factors for proximal junctional failure in spine surgery, but an unbalanced or hyper corrected spine is now considered as one of the main reasons for implant and junctional failure. 36,37…”
Section: Discussionmentioning
confidence: 99%
“…Xu 23 (2020) 143 UH, values of the vertebral body and pedicle as predictors of post-surgical pedicular screw loosening.…”
mentioning
confidence: 99%